Interdisciplinary Islamic Studies: Reconstructing Sciences for Maqāṣid-Based Islamic Economics in Digital Finance - Nafis, Muhammad Danial; Khusnudin (Institut Bisnis dan Informatika Kesatuan, 2026)
The rise of modern science has created an epistemological crisis separating spiritual values from social praxis, requiring Islamic studies to integrate revelation, reason, and empirical reality. This study aims to describe the basic concepts of an interdisciplinary and multiparadigm approach in Islamic studies, analyze its relevance in the reconstruction of Islamic sciences, and identify its role in building an Islamic economy based on maqāṣid al-syarīah, particularly in responding to contemporary phenomena such as cryptocurrency and digital finance. This study uses a qualitative literature approach. It finds that an interdisciplinary and multiparadigm approach is both a philosophical foundation and a practical method for reconstructing Islam’s role in civilization. By integrating positivist, interpretive, and critical paradigms, it offers comprehensive analyses of contemporary Islamic phenomena. In Islamic economics, this approach is crucial for evaluating cryptocurrency, addressing legal, ethical, and technological challenges beyond traditional fiqh, while aligning with maqāṣid al-shari’ah. This study concludes that an interdisciplinary and multiparadigm approach is a necessity for the revitalization of the Islamic intellectual tradition and for making Islam relevant.